Systematic review and meta-analysis of endorectal advancement flap and ligation of the intersphincteric fistula tract for cryptoglandular and Crohn's high perianal fistulas. Issue 3 (21st January 2019) - Stellingwerf, M E; van Praag, E M; Tozer, P J; Bemelman, W A; Buskens, C J
Abstract: Background: High perianal fistulas require sphincter-preserving surgery because of the risk of faecal incontinence. The ligation of the intersphincteric fistula tract (LIFT) procedure preserves anal sphincter function and is an alternative to the endorectal advancement flap (AF). The aim of this study was to evaluate outcomes of these procedures in patients with cryptoglandular and Crohn's perianal fistulas. Methods: A systematic literature search was performed using MEDLINE, Embase and the Cochrane Library. All RCTs, cohort studies and case series (more than 5 patients) describing one or both techniques were included. Main outcomes were overall success rate, recurrence and incontinence following either technique. A proportional meta-analysis was performed using a random-effects model. Results: Some 30 studies comprising 1295 patients were included (AF, 797; LIFT, 498). For cryptoglandular fistula (1098 patients), there was no significant difference between AF and LIFT for weighted overall success (74·6 (95 per cent c.i. 65·6 to 83·7) versus 69·1 (53·9 to 84·3) per cent respectively) and recurrence (25·6 (4·7 to 46·4) versus 21·9 (14·8 to 29·0) per cent) rates. For Crohn's perianal fistula (64 patients), no significant differences were observed between AF and LIFT for overall success rate (61 (45 to 76) versus 53 per cent respectively), but data on recurrence were limited. Incontinence rates were significantly higher after AF compared with LIFT (7·8 (3·3 to 12·4) versus 1·6 (0·4 to 2·8) per cent). Conclusion: Overall success and recurrence rates were not significantly different between the AF and LIFT procedure, but continence was better preserved after LIFT. Graphical Abstract: This systematic review and meta-analysis, including 1295 patients in 30 studies, suggested that, for cryptoglandular fistula, overall success and recurrence rates after the advancement flap and ligation of the intersphincteric fistula tract (LIFT) procedure are comparable. In Crohn's fistula, overall success rates after the two procedures were also comparable, although data were limited and no study reported recurrence rates after the LIFT procedure. For both indications, continence seems to be preserved better after the LIFT procedure. Treatment of high perianal fistulas